Improved Efficacy of Proton Pump Inhibitor – Amoxicillin – Clarithromycin Triple Therapy for Helicobacter pylori Eradication in Low Clarithromycin Resistance Areas or for Tailored Therapy. Issue 4 (29th January 2013) - Prasertpetmanee, Sanchai; Mahachai, Varocha; Vilaichone, Ratha‐korn
<x xml:space="preserve">Abstract</x> Objective Standard triple therapy for Helicobacter pylori eradication is no longer effective as an empiric choice in most areas. Even in low clarithromycin resistance areas, results ≥95% are infrequently achieved. This study was designed to search for a version of standard triple therapy for use low prevalence areas or as tailored therapy that is highly effective irrespective of CYP2C19 genotype. Design Two prospective pilot single center studies were performed in Thailand. H. pylori‐infected subjects were randomized to 7‐ or 14‐day regimens using a high‐dose proton pump inhibitor (PPI) triple therapy consisting of lansoprazole (60 mg) twice daily, amoxicillin 1 g twice daily, and long‐acting clarithromycin MR 1 g once daily. H. pylori was defined as positive H. pylori culture; or two positive tests (rapid urease test and histology); CYP2C19 genotyping was performed. H. pylori eradication was evaluated by 13C‐UBT 4 or more weeks after treatment. Results Hundred and ten subjects were enrolled (55 each to the 7‐ and 14‐day regimens). Antibiotic susceptibility testing (25 strains) showed 40% metronidazole resistance but no clarithromycin resistance. CYP2C19 genotyping (64 subjects) revealed 56.3% rapid metabolizer, 29.7% intermediate metabolizer, and 14% poor metabolizer. The eradication rate with the 14‐day regimen was 100% (95% CI = 93.5–100%) and 92.7% (95% CI = 82–97%) with the 7‐day regimen. The difference was related to improved eradication at 14 days in rapid metabolizers (i.e. 100 vs 88.2%). Conclusion Triple therapy using a 14‐day high‐dose PPI and long‐acting clarithromycin provided an excellent cure rate (100%) regardless of the CYP2C19 genotype.